In Vitro Effects of Strontium on Proliferation and Osteoinduction of Human Preadipocytes - V. Nardone; R. Zonefrati; C. Mavilia; C. Romagnoli; S. Ciuffi; S. Fabbri; G. Palmini; G. Galli; A. Tanini; M. L. Brandi (Stem Cells International)
Development of tools to be used for in vivo bone tissue regeneration focuses on cellular models and differentiation processes. In searching for all the optimal sources, adipose tissue-derived mesenchymal stem cells (hADSCs or preadipocytes) are able to differentiate into osteoblasts with analogous characteristics to bone marrow mesenchymal stem cells, producing alkaline phosphatase (ALP), collagen, osteocalcin, and calcified nodules, mainly composed of hydroxyapatite (HA). The possibility to influence bone differentiation of stem cells encompasses local and systemic methods, including the use of drugs administered systemically. Among the latter, strontium ranelate (SR) represents an interesting compound, acting as an uncoupling factor that stimulates bone formation and inhibits bone resorption. The aim of our study was to evaluate the in vitro effects of a wide range of strontium (Sr2+) concentrations on proliferation, ALP activity, and mineralization of a novel finite clonal hADSCs cell line, named PA20-h5. Sr2+ promoted PA20-h5 cell proliferation while inducing the increase of ALP activity and gene expression as well as HA production during in vitro osteoinduction. These findings indicate a role for Sr2+ in supporting bone regeneration during the process of skeletal repair in general, and, more specifically, when cell therapies are applied.